Altered static and dynamic amplitude of low-frequency fluctuations in acute carbon monoxide poisoning patients: a resting-state fMRI study - Wang, Shenghai; Sun, Tianze; Han, Wenxuan; Lin, Xiaoying; Zhang, Jiaqi; Peng, Yihao; Ma, Mingyue; Sheng, Wei; Zhang, Ming; Li, Haining (Frontiers in Neuroscience, 2026)
ObjectiveThis study aimed to investigate alterations in brain activity due to acute carbon monoxide poisoning (ACOP) and their relationship with clinical manifestations using static and dynamic amplitude of low-frequency fluctuation (ALFF) analyses.MethodsResting-state functional magnetic resonance imaging (fMRI) and clinical data were obtained from 31 ACOP patients and 28 healthy controls. The static ALFF value and dynamic ALFF variability were measured and compared between groups. Partial correlation analysis explored the relationships between changes in ALFF and clinical features in ACOP patients.ResultsACOP patients exhibited increased dynamic ALFF in the bilateral superior frontal gyrus (SFG) and left middle frontal gyrus (MFG) and decreased static ALFF in the left middle occipital gyrus (MOG) compared to controls. Aberrant dynamic ALFF in the left SFG and MFG was negatively correlated with MoCA-B scores (r = −0.430, p = 0.036; r = −0.439, p = 0.032).ConclusionACOP patients exhibited abnormal instability in intrinsic brain activity, particularly in prefrontal areas, where temporal variability in local brain activity correlates with cognitive performance. This study highlights the value of combined static and dynamic ALFF approaches in understanding brain disturbances caused by CO exposure, providing new insights into the neuropathological mechanisms of ACOP.